Interactive effects of life history and season on size‐dependent growth in juvenile Atlantic salmon. Issue 4 (30th April 2013) - Sigourney, Douglas B.; Letcher, Benjamin H.; Obedzinski, Mariska; Cunjak, Richard A.
Abstract: Size‐dependent growth (SDG) is an important process in structuring populations as well as determining life history outcomes. Despite its importance, there have been few investigations from observational studies focusing on the interaction between life history decisions and SDG. In this study, we used data on individually tagged Atlantic salmon from both the laboratory and the field to investigate differences in SDG among two life history groups, parr and smolts. In the laboratory, we found little evidence of SDG in parr but seasonally dependent SDG in the smolt group. Smolts showed at strong compensatory response over the winter months just prior to the smolt transformation window. In the field, we found little evidence of SDG early in ontogeny (i.e., age 0+ fall and winter). There was some evidence of depensatory growth (positive SDG) during the age 1+ spring among both life history groups that may reflect random habitat variation or the monopolisation of resources. After the age 1+ spring, we found that smolts were more likely to show a compensatory effect (negative SDG) than parr. This effect was strongest, as they approached the smolt window in the spring of their age 2+ year. These results suggest (i) SDG is common in Atlantic salmon; however, the form and extent of life history depends on (ii) season and (iii) life history. For individuals that adopt a smolt life history, trade‐offs between freshwater survival and sea survival may lead to a convergent growth pattern, as they approach the smolt migration window.